IMPACT OF CHANGES TO THE DIGITALIZATION SYSTEM ON EMPLOYEE PERFORMANCE: LITERATURE REVIEW STUDY - Gunawan, Egit Fahri; Sopiah, Sopiah (Universitas Islam Malang, 2025)
Digitizing changes in employee performance. In this digital era, Human Resources (HR) is very important or very much needed. Management of Human Resources (HR) must be integrated with technological developments to achieve effectiveness and efficiency. Employees are the most important people in realizing the vision, mission and goals of an organization. Employee performance is one of the metrics that companies must consider. Creating a company with superior quality requires improving employee performance by improving skills. This is an opportunity for the organization or company to increase the productivity of others, such as employee work assignments. This research method adopts a literature search method. The method used is a literature survey using secondary data, where the authors collect data on a related topic and extract information from various Scopus indexed journals. This article aims to review the effect of digitization on employee performance. The results of this literature review section suggest that changes in digitization can affect employee performance in organizations or companies.